2020
DOI: 10.1186/s12974-020-01924-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A inhibits astrocyte migration via activating p38 MAPK

Abstract: Background: The accumulation of astrocytes around senile plaques is one of the pathological characteristics in Alzheimer's disease (AD). Serum amyloid A (SAA), known as a major acute-phase protein, colocalizes with senile plaques in AD patients. Here, we demonstrate the role of SAA in astrocyte migration. Methods: The effects of SAA on astrocyte activation and accumulation around amyloid β (Aβ) deposits were detected in APP/PS1 transgenic mice mated with Saa3 −/− mice. SAA expression, astrocyte activation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
(75 reference statements)
2
22
0
Order By: Relevance
“…41 Moreover, activation of the p38 pathway has been shown to inhibit mouse astrocyte and human glioma U251 cell migration upon serum amyloid A treatment. 49 Consistent with our result, EGCG could inhibit the growth and invasion of pancreatic cancer in xenografted mice by reducing ERK activity but enhancing p38 activity. 50 Therefore, our results could suggest that the attenuated survival and migration in primary pterygium cells after green tea extract and EGCG treatments could be associated with the reduction in ERK p42/p44 pathway and elevation in p38 pathway activation.…”
Section: ■ Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…41 Moreover, activation of the p38 pathway has been shown to inhibit mouse astrocyte and human glioma U251 cell migration upon serum amyloid A treatment. 49 Consistent with our result, EGCG could inhibit the growth and invasion of pancreatic cancer in xenografted mice by reducing ERK activity but enhancing p38 activity. 50 Therefore, our results could suggest that the attenuated survival and migration in primary pterygium cells after green tea extract and EGCG treatments could be associated with the reduction in ERK p42/p44 pathway and elevation in p38 pathway activation.…”
Section: ■ Discussionsupporting
confidence: 90%
“…EGCG could also inhibit the viability and migration of human thyroid carcinoma cells through reduction of ERK1/2 phosphorylation . Moreover, activation of the p38 pathway has been shown to inhibit mouse astrocyte and human glioma U251 cell migration upon serum amyloid A treatment . Consistent with our result, EGCG could inhibit the growth and invasion of pancreatic cancer in xenografted mice by reducing ERK activity but enhancing p38 activity .…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that SAA1 overexpression in APP transgenic mice promotes the accumulation of Aβ in the brain and increases gliosis [36]. Conversely, APP overexpression was also found to increase SAA1 and SAA3 deposition in the brain [36,37]. However, SAA3 was shown to inhibit astrogliosis in Aβ-overproducing APP/PS1 mice, indicating that the functions of SAA in the brain may differ by isoform and depend on the conditions of expression.…”
Section: Discussionmentioning
confidence: 99%
“…SAA is highly upregulated by the liver during an acute inflammatory insult, and the magnitude of increase indicates the severity of the systemic inflammatory response [34]. SAA can also cross the intact BBB, and it has been shown to contribute to plaque deposition and to regulate gliosis [35][36][37][38] and depressive-like behaviors [39]. Thus, we also evaluated concentrations of soluble and insoluble SAA in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…2021, 22, x FOR PEER REVIEW 2 of 13 Serum amyloid A (SAA), an evolutionarily highly conserved acute phase protein in vertebrates and invertebrates, is predominantly secreted by hepatocytes in the liver and is also produced by a variety of cells and tissues [9][10][11]. In fields of regulating inflammation and immunity and lipid metabolism, SAA protein plays an important role that benefits the body [6,11,12]. SAA is an important amyloid precursor and plays a key role in AA amyloidosis which impacts ∼1% of patients with chronic inflammation [13,14].…”
Section: Introductionmentioning
confidence: 99%